THE IMPLICATION OF TOLERANCE VALUE IN CHARACTER EDUCATION OF MULTICULTURAL COMMUNITY IN KAMPONG JAWA DENPASAR-BALI - Wafda Zulfa; Mualamatul Musawamah; Rizqi Niken Hawa; Septi Naila Ulya; Muhammad Ulil Fahmi (Paedagogia: Jurnal Pendidikan, 2023)
Cultural diversity in a multicultural society owned by Indonesia does not escape the values of tolerance. The application of the value of tolerance not only respects and respects differences in beliefs, customs, cultures, languages, etc., but must also be balanced with an open and airy attitude in order to create a sense of security and comfort to others by showing diversity in attitude, customs, culture, and religion. Each multicultural society has its own character education, just like the multicultural community in Kampung Jawa Denpasar-Bali. Character education will be stronger if there are implications of the value of tolerance for character education. This study aims to describe the early history of the establishment of this Javanese village so that it can exist until now, what values of tolerance are applied in the life of a multicultural society so that it can live in harmony side by side, and the relationship of the value of tolerance in the character education of multicultual communities in Kampung Jawa Denpasar-Bali. This research uses qualitative methods with a phenomenological approach. From this research, it can be concluded that there are implications for the value of tolerance for multicultural community character education in Kampung Jawa Denpasar-Bali, namely making it a society that has a sense of harmony between religious people, has a sense of social concern between religious people, and mutual respect and mutual respect between religious people.